Analisis Manajemen Layanan Teknologi Informasi Perpustakaan SMK Negeri 5 Palembang Menggunakan Framework ITIL - Muhammad Zaki; Tata Sutabri (JSAI (Journal Scientific and Applied Informatics), 2023)
This study aims to analyze the maturity level of library system service management at SMK Negeri 5 Palembang and provide recommendations to achieve the expected maturity level. Data obtained from interviews and direct observation of system users and respondents were determined using the RACI diagram. From the results of observations it was found that in the services provided by the library system, books were often found that did not have a storefront or storage stock but were still recorded in the system, besides that the speed of accessing the system was slow, alumni data was still recorded in the system which should have been deleted when the student graduated because basically this system is only intended for members who are still active in the school environment. The maturity level of library system services has never been measured, so it is not yet known whether the system service management is in accordance with the vision and mission to be achieved by the school. The measurement uses the ITIL Version 3 framework with the Service Operation domain. From the results of distributing questionnaires to respondents consisting of students, teachers and librarians, it was found that the maturity level of the library system at SMK Negeri 5 Palembang is at 2.79 which means it is at level 3, namely defined. While the expected maturity level is level 4, namely managed, GAP analysis is worth 1.20. recommendations are given to the library to be able to reach the level of expectations and be able to overcome the problems found. Keywords: Library system, SMK Negeri 5 Palembang, Maturity Level, ITIL V3, Service Operations